The EU apportionment formula: insights from a business case - Roggeman, Annelies; Verleyen, Isabelle; Cauwenberge, Philippe Van; Coppens, Carine (Journal of Business Economics and Management, 2013)
In this paper we use firm level data from a listed multinational to investigate how several designs for the Common Consolidated Corporate Tax Base (CCCTB) formula could affect the allocation of the consolidated tax base. The design is relevant in the light of member states’ concern for protecting their tax revenues, as well as for the multinational companies’ tax minimizing possibilities. Moreover, it plays an important role in achieving an efficient and simple tax system. Simulating different apportionment formulas, the results show that including more factors and using more equal weights distributes the common tax base more equally, which could reduce the incentive to shift factors from high to low tax countries. The results also indicate that simplifying the factor definitions, leads to rather minor changes in the allocation. Using unpublished data, this study allows to investigate the consequences of different formulas in detail, which contributes to the current discussion on corporate tax harmonization in the EU.